The Benefits of Low-Carbohydrate, High-Fat (LCHF) Diet on Body Composition, Leg Volume, and Pain in Women with Lipedema - Małgorzata Jeziorek; Angelika Chachaj; Monika Sowicz; Agnieszka Adaszyńska; Aleksander Truszyński; Justyna Putek; Krzysztof Kujawa; Andrzej Szuba (Journal of Obesity)
This study aimed to assess the potential benefits of a low-carbohydrate, high-fat (LCHF) diet on body composition, leg volume, and pain reduction in women with lipedema compared to overweight or women with obesity. The study included 113 female participants, 56 with lipedema and 57 with overweight/obesity (BMI >25 kg/m2) without lipedema. All subjects were prescribed a low-carbohydrate, high-fat (LCHF) diet with anti-inflammatory properties to adhere to for a duration of 7 months. Measurements of anthropometry, body weight, composition, and pain (VAS) were conducted at the study’s commencement and conclusion. 52 participants completed the study. Both groups experienced a similar weight reduction, amounting to 12.9% compared to the baseline (−10.8 kg vs. −11.9 kg; p = 0.14, for lipedema and women with overweight/obesity, respectively). The most reduction was in body fat mass. Improvements in various parameters were observed, except for ankle circumferences, which decreased more in the lipedema group. Lipedema participants showed significantly reduced pain levels following the LCHF diet (4.6 ± 2.6 vs 3.0 ± 2.3; p < 0.001). The LCHF diet holds promise for weight loss, body fat reduction, leg volume management, and pain alleviation in women with lipedema. These findings provide valuable insights into potential therapeutic strategies for lipedema management.